2009
DOI: 10.1177/000313480907500512
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy during Otolaryngology Residency: Experience and Recommendations

Abstract: Pregnancy during graduate medical training became a pertinent issue in the United States during the 10-year interval between 1992 and 2002 as the number of female residents trended steadily upward to over 25 per cent. Surgical training programs characteristically present unique challenges and stressors for all trainees, and pregnancy introduces additional physical, professional, and emotional demands for the pregnant woman and her coworkers. A qualitative study was performed using in-person interviews of femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 8 publications
1
38
0
2
Order By: Relevance
“…This suggests positive changes over time: a 1988 national survey 12 indicated that only 16% of physicians found their workplace to be supportive of pregnancy and 12% to be supportive during their child's infancy. Although this may reflect an impact of cultural and legislative changes over time, such as the U.S. Family and Medical Leave Act of 1993, it is important to note that a 2009 survey 29 reported that 36% of program directors actively discouraged pregnancy during residency and department chairs viewed pregnancy during residency as a hardship on other residents and an interference on the smooth functioning of a department. Thus, although heartening, it is possible that self-selection effects (by which primarily those women training in supportive programs chose to pursue pregnancy during training) may influence our findings.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests positive changes over time: a 1988 national survey 12 indicated that only 16% of physicians found their workplace to be supportive of pregnancy and 12% to be supportive during their child's infancy. Although this may reflect an impact of cultural and legislative changes over time, such as the U.S. Family and Medical Leave Act of 1993, it is important to note that a 2009 survey 29 reported that 36% of program directors actively discouraged pregnancy during residency and department chairs viewed pregnancy during residency as a hardship on other residents and an interference on the smooth functioning of a department. Thus, although heartening, it is possible that self-selection effects (by which primarily those women training in supportive programs chose to pursue pregnancy during training) may influence our findings.…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 ] Other stressors include an unpredictable work schedule and the difficulty of breastfeeding after maternity leave. [ 26 , 27 ] The inherent stress of early parenthood is compounded by the lack of institutional resources, as only 38% of academic hospitals have on-site childcare and less than 60% have lactation spaces. [ 10 ] Workplace stigma against pumping breast milk at work and the lack of time to do so may impact the duration of breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…The metaanalysis of Finch became a cornerstone in the field of studying fertility disorders among female physicians, since it showed that health problems during pregnancy occurred more frequently among house officers and young female doctors [ 7 ]. A higher rate of health disorders during pregnancy was confirmed by two quantitative investigations [ 8 , 9 ], and a higher rate of preterm births was found in a survey of Canadian female surgeons [ 8 – 10 ]. Hamilton et al also found a higher rate of preterm deliveries among female surgeons, compared with the general female population [ 11 ].…”
Section: Introductionmentioning
confidence: 91%